Polydextrose-driven gut microbiota modulation from synbiotic yogurt intake simulated in the in vitro dynamic multivessel colonic xGIbiomics system - Pessotti, Rita de Cassia; Salgaço, Mateus; Agostinho, Laira Lorraine; de Freitas, Miller Nunes; Bogsan, Cristina Stewart Bittencourt; Guimaraes, Cristiano Ruch Werneck; Sivieri, Katia (Frontiers in Nutrition, 2025)
IntroductionThe gut microbiota plays a pivotal role in maintaining host health and dietary strategies, such as synbiotic interventions, have emerged as promising tools to modulate its composition and metabolic activity. Inulin is a well established prebiotic, but alternative fibers like polydextrose have gained interest due to their distinct fermentation profiles and functional benefits. This study aimed at evaluating whether polydextrose could exert prebiotic effects comparable to inulin when incorporated into a synbiotic yogurt containing Bifidobacterium animalis subsp. lactis BB-12®.MethodsUsing the in vitro dynamic multivessel colonic xGIbiomics® system, we simulated human gut conditions and assessed changes in microbial composition and metabolite production.ResultsBoth synbiotic yogurts increased levels of beneficial organic acids, such as propionate and lactate, and decreased ammonium ion concentrations, indicating a shift toward saccharolytic fermentation. The synbiotic formulation incorporating polydextrose also led to increased butyrate production when compared to the yogurt containing only the BB-12® probiotic, and a greater relative abundance of Bifidobacterium spp. when compared to the synbiotic formulation incorporating inulin. Additionally, both synbiotic treatments reduced Klebsiella spp., a potentially pathogenic genus.DiscussionThese findings highlight polydextrose as a viable and effective alternative to inulin in synbiotic formulations, reinforcing its potential as a functional dietary fiber for gut health modulation.